Nutrient Acquisition and Metabolism by Campylobacter jejuni - Stahl, Martin; Butcher, James; Stintzi, Alain (Frontiers in Cellular and Infection Microbiology, 2012)
The gastrointestinal pathogen Campylobacter jejuni is able to colonize numerous different hosts and compete against the gut microbiota. To do this, it must be able to efficiently acquire sufficient nutrients from its environment to support its survival and rapid growth in the intestine. However, despite almost 50 years of research, many aspects as to how C. jejuni accomplishes this feat remain poorly understood. C. jejuni lacks many of the common metabolic pathways necessary for the use of glucose, galactose, or other carbohydrates upon which most other microbes thrive. It does however make efficient use of citric acid cycle intermediates and various amino acids. C. jejuni readily uses the amino acids aspartate, glutamate, serine, and proline, with certain strains also possessing additional pathways allowing for the use of glutamine and asparagine. More recent work has revealed that some C. jejuni strains can metabolize the sugar L-fucose. This finding has upset years of dogma that C. jejuni is an asaccharolytic organism. C. jejuni also possesses diverse mechanisms for the acquisition of various transition metals that are required for metabolic activities. In particular, iron acquisition is critical for the formation of iron-sulphur complexes. C. jejuni is also unique in possessing both molybdate and tungsten cofactored proteins and thus has an unusual regulatory scheme for these metals. Together these various metabolic and acquisition pathways help C. jejuni to compete and thrive in wide variety of hosts and environments.